Javanese Tradisional Healing dalam Pemulihan Pasca Persalinan pada Ibu Bersalin Normal di Era Modern - Yunia Renny Andhikatias; Megayana Yessy Maretta; Nurul Devi Andriani (Sekolah Tinggi Ilmu Kesehatan AKBIDYO, 2021)
Background: Postpartum care which can be handled by complications such as the entry of germs into the uterus, both exogenously and endogenously. One form of treatment for postpartum mothers who adhere to the old culture is consuming herbal remedies, either homemade or factory-made. Jamu which is a traditional herb, has been widely accepted in almost all countries in the world. According to WHO, countries in Africa, Asia and Latin America use traditional herbal medicine as a complement to primary medicine. Apart from herbal medicine, other postpartum treatments from Java are bengkung, pilis and massage. Objective: To find out whether Javanese Traditional Healing has significant benefits for informants in the postpartum recovery process. Benefit: It is hoped that this study will be a reference in postpartum treatment. Research Method: Qualitative study of phenomenology. The sampling technique used purposive random sampling. With the number of key informants as many as 5 people. Data obtained by interviewing 5 key informants and 4 triangulation informants. Results: The results showed that all of the informants performed Javanese Traditional Healing. 4 informants drank the herbal medicine carrying, did massage, used bengkung and pilis, while 2 informants drank the 40- day herbal sachet specifically for the postpartum period, performed massages and used curves. During consuming herbal medicine, doing massage and wearing curves, information states that her JAVANESE TRADISIONAL HEALING DALAM PEMULIHAN PASCA PERSALINAN PADA IBU BERSALIN NORMAL DI ERA MODEREN Jurnal Ilmu Kebidanan, Volume 9 Nomor 1 Tahun 2021 •42 breast milk is getting heavier, her body is fit, sleep quality improves and her weight slowly returns to normal. No complaints were made. Conclusion: The composition of the herbal medicine consumed by the informants can provide a smoothing effect of breastfeeding and make the body of the infoman fresher and maintain body weight coupled with postpartum massage which is carried out after childbirth. Meanwhile, Bengkung does not believe in maintaining the shape of the stomach and supports the spine so that it is not sore. Keywords: Jamu, Traditional, Massage, Bengkung, Postpartum, Postpartum